2011
DOI: 10.1097/sla.0b013e31821fd1ce
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopy in Combination with Fast Track Multimodal Management is the Best Perioperative Strategy in Patients Undergoing Colonic Surgery

Abstract: Optimal perioperative treatment for patients requiring segmental colectomy for colon cancer is laparoscopic resection embedded in a FT program. If open surgery is applied, it is preferentially done in FT care. This study was registered under NTR222 (www.trialregister.nl).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

29
512
5
13

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 695 publications
(583 citation statements)
references
References 29 publications
29
512
5
13
Order By: Relevance
“…It may also reduce the prevalence of postoperative immunosuppression [111] while providing equivalence in cancer outcomes [112][113][114][115][116]. The debate during the last 5 years has centred around whether open surgery undertaken within an ERAS programme can match laparoscopic resection which is similarly optimised.…”
Section: Laparoscopy and Modifications Of Surgical Accessmentioning
confidence: 99%
See 1 more Smart Citation
“…It may also reduce the prevalence of postoperative immunosuppression [111] while providing equivalence in cancer outcomes [112][113][114][115][116]. The debate during the last 5 years has centred around whether open surgery undertaken within an ERAS programme can match laparoscopic resection which is similarly optimised.…”
Section: Laparoscopy and Modifications Of Surgical Accessmentioning
confidence: 99%
“…Readmission rates of [20 % were high in both arms of the first trial and in the open group of the second trial, but acceptable at 5 % in the laparoscopic arm of the latter trial. Recently, the Laparoscopy and/or Fast-track Multimodal Management Versus Standard Care (LAFA) study reported the results from its multicentre RCT which randomised between laparoscopic and open segmental colectomy within 9 Dutch centres [111]. The median primary and total stay in hospital was 2-days shorter after laparoscopic resection.…”
Section: Laparoscopy and Modifications Of Surgical Accessmentioning
confidence: 99%
“…This is possibly owing to the fact that it is an initial, reduced number of patients. The LAFA study shows similar results as regards morbidity in the four groups compared (laparoscopic surgery with and without ERAS and conventional surgery with and without ERAS), but clearly defines the benefits of combining both of these minimally invasive techniques, which translate into early discharge without a higher readmission rate in the case of laparoscopy with ERAS, considering it as a parameter of best outcome [15]. On the other hand, a metaanalysis published recently evaluates 6 prospective randomised trials of malignant colorectal disease operated laparoscopically with and without an ERAS protocol.…”
Section: Discussionmentioning
confidence: 58%
“…The Dutch prospective randomised LAFA trial, published in 2011, clearly shows how the patients who underwent laparoscopy benefited from multimodal care, with a shorter hospital stay and lower costs than those who were under conventional care and had undergone laparoscopy or open surgery [15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation